Pick a number : internationalizing U.S. accounting - Hussey, Roger. (2014 digital library., 2014)
For many years, individual countries decided their own rules and regulations for company financial accounting and reporting. As the world became more global, problems began to arise. A company could make a profit for the year if the rules in its own country were applied, but this could turn into a loss if another country's rules were used. This did not make sense. Investors were hesitant to buy shares in foreign companies, companies were careful when the financial stability of foreign suppliers and customers could not be established, and companies wanting to list on a foreign stock exchange, for example, New York, experienced difficulties. To prevent this confusing and misleading state of affairs, attempts were made at the international level to agree on what the rules, known as accounting standards, should be for financial accounting and reporting. Those standards are now issued by the International Accounting Standards Board (IASB). Since 2002, the standard setter in the United States, the Financial Accounting Standards Board (FASB), has been actively engaged with the IASB in attempting to converge U.S. regulations with international accounting standards. These events are not only important to accountants, but to everyone who has been dealing with a company. This could be investors, employees, customers, banks, suppliers, and the tax authorities. If you are interested in the financial performance and status of a company, you need to understand the accounting rules, their changes, and the reasons they pursue an international set of standards.